Retinal pigment epithelium melanin distribution estimated by polarisation entropy and its association with retinal sensitivity in patients with high myopia. Issue 10 (6th May 2021) - Harimoto, Akira; Obata, Ryo; Yamamoto, Motoshi; Aoki, Nobuyori; Yamanari, Masahiro; Sugiyama, Satoshi; Kitano, Marie; Fujita, Asahi; Minami, Takahiro; Ueda, Kohei; Azuma, Keiko; Inoue, Tatsuya; et al.
Abstract : Purpose: To investigate retinal sensitivity of highly myopic eyes without choroidal neovascularisation (CNV) or patchy chorioretinal atrophy (PCA) and investigated its association with anatomical characteristics including melanin distribution at the retinal pigment epithelium (RPE), which was evaluated with polarisation-sensitive optical coherence tomography (PS-OCT). Design: Retrospective consecutive observational cohort study. Methods: We included highly myopic eyes (refractive error ≤−8.0 dioptres or axial length of ≥26.5 mm) from patients at the University of Tokyo Hospital. Retinal sensitivity was measured by microperimetry at 25 sectors within 6 degrees from the fovea. Depolarisation value, which reflected melanin pigmentation, was measured by a clinical prototype of PS-OCT and was parameterised as polarimetric entropy. Retinal sensitivity or entropy at the RPE in high myopia was compared with emmetropic control subjects. The association of retinal sensitivity with age, axial length, entropy, or choroidal thickness was assessed in per-eye and per-sector analysis. Results: Twenty-three highly myopic eyes (age, 66.6±12.3 years) were included. The average retinal sensitivity was 25.3±3.0 dB, which was significantly decreased compared with the control (p<0.0001). The average entropy at the RPE in the highly myopic eyes was significantly lower than in the control (p<0.0001). Univariate analysis followed by multivariate analysis showed that besides age, axial length or choroidal thickness, RPE entropy was independently associated with retinal sensitivity (β=4.4; 95% CI 0.5 to 8.3; p=0.03). Conclusions: Decreased depolarisation at the RPE measured with PS-OCT, which reflected altered melanin pigmentation, was independently associated with reduced retinal sensitivity in patients with early stages of myopic maculopathy without CNV or PCA.